Penerapan Model Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar Siswa SDN 32 Bengkulu Selatan - Kartika Herleni; Irfan Supriatna (JURIDIKDAS, 2023)
The research aims to describe the application steps of the Discovery Learning model and analysis the student's motivations and learning outcomes thematic for third grade students in SDN 32 Bengkulu Selatan. This in tipe of research is third grade students conducted in two cycles. This research subject is a teacher and third grade students. The research instruments used were observation sheets, test sheets and questionnaire. Observation and questionnaire data analysis techniques use the average formula scores, the highest score, the lowest score, the scoring gap, and the value range for each criteria.  Average formula score the students and acuity of learning. The average result of student cycle I 77% with category good increases in cycle II which is 87% with category excellent. Accordingly, the average result of student study increases from cycle I to category good increases to excellent on cycle II. Thus, it can be concluded that the application of the Discovery Learning model to thematic learning can improve the motivation and learning outcomes of third grade students in SDN 32 Bengkulu Selatan.